Young female handball players and sport specialisation: how do they cope with the transition from primary school into a secondary sport school? - Kristiansen, E.; Stensrud, T. (British Journal of Sports Medicine, 2017)
Objective The aim of the present study was to examine how six young female handball players (aged 13-14 years) perceived the transition from primary school to a sport-specialised secondary school.